Microencapsulated parathyroid allotransplantation in the omental tissue. Issue 10 (19th June 2019) - Yucesan, Emrah; Basoglu, Harun; Goncu, Beyza; Akbas, Fahri; Ersoy, Yeliz Emine; Aysan, Erhan
Abstract: Permanent hypoparathyroidism is a severe clinical condition accompanied by low parathyroid hormone level. Conventional treatment requires lifelong medication, and daily drug usage has some side effects. To avoid this circumstance, transplantation is an alternative and curative option. Microencapsulation may be used as a transplantation approach particularly to evade immune response. In order to define treatment of permanent hypoparathyroidism, a 37‐year‐old female recipient who has permanent hypoparathyroidism was evaluated for 3 years. Routine tests, viral markers, and T and B lymphocyte cross‐match tests were analyzed. In addition intradermal skin test was performed for ultrapure alginate. Microencapsulation of cultured parathyroid cells was performed with ultrapure alginate. Cell suspension was prepared and spheroids were generated with calcium chloride. Afterward, transplantation was performed with a laparoscopic approach in the omental tissue. The recipient was discharged from the hospital without complications. Serum calcium, parathyroid hormone (PTH), and phosphorus levels were observed throughout 1 year. During the follow‐up period, no complications were observed. Serum calcium levels were increased significantly on day 10 and PTH levels were increased on day 25 as well. According to our knowledge, this is the first study where ultrapure alginate‐based microencapsulated parathyroid cells were transplanted in the omental tissue. A significant increment of PTH levels was detected. Microencapsulated parathyroid cells showed the functionality of this technique for more than 1 year. This study showed that using ultrapure alginate‐based microencapsulation without immunosuppression appears to be a promising technique.